Gut microbiota aberrations precede diagnosis of gestational diabetes mellitus - Kati Mokkala; Noora Houttu; Tero Vahlberg; Eveliina Munukka; Tapani Rönnemaa; Kirsi Laitinen (My University, 2022)
Recent evidence has shown the importance of gut microbiota in human metabolic health [1]. Gut microbiota dysbiosis in turn has been associated with the development of a wide range of metabolic diseases, including type two diabetes [1]. Whether microbiota composition contributes to the development of GDM, the common condition in pregnant women, is currently unknown. We hypothesized that gut microbiota may be involved in the development of GDM, possibly through inflammation-driven alterations in glucose metabolism [2].
We measured whether gut microbiota composition in early pregnancy differs in women who developed GDM from that of women who did not develop GDM in later pregnancy.